2015
DOI: 10.1007/s10750-015-2201-9
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope analysis reveals relative influences of seasonal hydrologic variation and impoundment on assimilation of primary production sources by fish in the Upper Yesilırmak River, Turkey

Abstract: This study analyzed variation in stable isotope ratios of aquatic and terrestrial primary producers and two common cyprinid fishes (Capoeta banarescui and Squalius cephalus) at seven sites in the upper Yeşilırmak River Basin, Turkey, to estimate relative contributions of basal production sources to fish biomass. We hypothesized that seasonal and spatial variation in fish assimilation of basal production sources would be affected by hydrological variation, with results for a reach downstream from a reservoir di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Given that the seston in the limnetic zone comprised mainly of planktonic algae, it is reasonable to conclude that autochthonous food sources (aquatic algae) in the Daning River serve as certain unneglectable and vital supports to fish production. This finding is consolidated by studies of other reservoirs [8,16] and rivers [39][40][41] where algal carbon of either suspended or benthic origin is considered to be of much importance.…”
Section: The Relative Importance Of Four Basic Carbon Sourcesmentioning
confidence: 82%
See 1 more Smart Citation
“…Given that the seston in the limnetic zone comprised mainly of planktonic algae, it is reasonable to conclude that autochthonous food sources (aquatic algae) in the Daning River serve as certain unneglectable and vital supports to fish production. This finding is consolidated by studies of other reservoirs [8,16] and rivers [39][40][41] where algal carbon of either suspended or benthic origin is considered to be of much importance.…”
Section: The Relative Importance Of Four Basic Carbon Sourcesmentioning
confidence: 82%
“…The perceptible difference in carbon pathway patterns in the Daning River relates to divergent landscape-scale hydrologic characteristics in the different reaches as described in many other riverine studies [8,13,16]. Due to the impoundment of the TGR, the lacustrine environment has been shaped in the downstream with water velocity sharply halted and water depth gradually deepening along the tributary.…”
Section: Spatial Variation Of Carbon Source Contributionmentioning
confidence: 94%
“…Third, studies have shown that enhanced autotrophic production in large reservoirs can lead to considerable quantities of additional planktonic primary production and organic matter (seston) being exported downstream via releases or spilling events (Marty, Smokorowski, & Power, ; Smokorowski et al, ). Living and detrital phytoplankton and zooplankton production from impoundments may represent a carbon source to downstream food webs that was previously unavailable and typically exhibit a characteristic δ 13 C signature that is more depleted than terrestrial primary production and benthic primary production (de Junet et al, ; Solomon et al, ), and these signatures can be detected in downstream food webs (e.g., Chen & Jia, ; Kaymak et al, ; Smokorowski et al, ). Taken together, our results for the Brisbane and Burnett Rivers suggest that reduced autochthonous carbon contributions below dams, coupled with increased availability of reservoir‐derived autochthonous carbon sources released from dams, may have caused lungfish to increasingly rely upon pelagic‐dominated from benthic‐dominated food sources over time.…”
Section: Discussionmentioning
confidence: 99%
“…Living and detrital phytoplankton and zooplankton production from impoundments may represent a carbon source to downstream food webs that was previously unavailable and typically exhibit a characteristic δ 13 C signature that is more depleted than terrestrial primary production and benthic primary production (de Junet et al, 2009;Solomon et al, 2011), and these signatures can be detected in downstream food webs (e.g., Chen & Jia, 2009;Kaymak et al, 2015;Smokorowski et al, 2011). Although subtle, it is interesting to note that δ 13 C of lungfish showed some evidence of a step decrease in the mid-1990s, when values consistently fell below −20‰ and then declined further to between −24‰ and −26‰ in present-day.…”
Section: Discussionmentioning
confidence: 99%
“…The research of this project has become the focus of world attention, and has provided an important theoretical reference for other countries to apply modern network technology in education (Kaymak, Winemiller, Akin, et al 2015). Mr. Mery, Pamela M took San Francisco Institute as the studied object, and carried out research on the integration of modern network technology and student service system and how to correctly apply modern network technology.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%